The Process of Metadata Management for Radar Target Classification Algorithm Development - Valenta, Vojtěch; Pidanič, Jan; Němec, Ondřej (IEEE (Institute of Electrical and Electronics Engineers), 2020)
This paper presents an approach to manage metadata (target class labels) for the recorded primary Doppler radar data. This information is necessary for further research and development of target classification algorithms. For this purpose, a labelling methodology and an application radar data analysis and target labelling was developed. The application includes radar records file processing, Doppler filtering, tag creation, data visualizationand tag database. For the better context of analysed data, an interface to Geographic Information Software (GIS) programis included as well. GIS program allows overlaying radar Plan Position Indicator (PPI) data with map data, airplane transponder tracks, drone flight path log and other support data. Finally, the application notes and observations are presented.
Proces Správy Metadat pro Vývoj Algoritmů Klasifikace Radarového Cíle
Keywords: primary radar; target classification; radar recordings; target type labelling; radar data analysis; primární radar; klasifikace cíle; radarové záznamy; štítkování cíle; analýza radiolokačních dat